Performance of a New Design Based on Substrate-Integrated Waveguide Slotted Antenna Arrays for Dual-Band Applications (Ku / K) - Turkiya Abes; Keltouma Nouri; Boubaker Seddik Bouazza; Kada Becharef (Journal of Communications Software and Systems, 2020)
This paper introduces and discusses the study of a new concept for SIW array antenna development. This conducted development is based on three designs, two of them related to 1x2 arrays fed by SIW line, combined with SIW inset line, and the last designed for 2X2 array antenna feed by SIW inset line. All these structures are designed to give dual-band at (Ku - K) bands with enhanced gain and bandwidth. The new 2x2 array antenna has a high gain, and it consists of four SIW cavities staggered patches with a 90° phase shift, which are fed using microstrip line shielded by SIW vias. The designs were conducted using full-wave simulator ANSYS HFSS - the frequency domain solver. The 2x2 array antenna gives a return loss about (-20 dB), a high gain of 9.05 dB, and two bandwidth equals 210 MHz and 1310 MHz respectively at both of the operating bands. To validate the simulated results the simulation was conducted again using the time-domain solver of the CST Microwave Studio (MWS) full-wave simulator. Simulation results obtained from the two software having different solvers were in good agreement in the results.